Anti-Bullying Counseling Strategy: Case Study at Wonotenggang Village Elementry School, Rowosari Distric - Naili Saadah; Akhmad Bagus Septiyoko; Ulya Latifatul Husna; Amalia Dahliana Nurhadi Putri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Bullying is a phenomenon that often occurs in society, even up to elementary school level. This research is about socialization carried out to prevent action bullying at SD N Wontenggang which is attended by students in grades four to six. The findings of this research are action socialization bullying This can be done through the implementation of prevention, the role of parents and teachers, as well as therapy through watching films together.